Estimation of passenger car CO2 emissions by population density class based on Japanese vehicle inspection certificate data - Keisuke Matsuhashi; Toshinori Ariga; Masahiro Ishikawa (IATSS Research, 2023)
Estimates of passenger car CO2 emissions that reflect regional characteristics are useful for predicting the effects of electrification, modal shifts in transport, and urban compactness. To date, differences in emissions have often been estimated based on the regional differences in the number of vehicles owned. Regional differences in mileage were estimated from the counts of the Origin and Destination Surveys in the Road Traffic Census. In this study, by utilizing the mileage data from the vehicle inspection certificate data, it was possible to reflect the differences in mileage per vehicle in detailed regional terms. The higher the population density, the smaller was the mileage per vehicle. Based on this, we calculated the CO2 emissions from passenger cars by municipality nationwide and estimated the CO2 emissions and population share by grid population density. In areas of 3000–10,000 persons/km2, which accounts for approximately 40% of Japan's population, emissions per person approximated the national average. However, in areas with 1000–3000 persons/km2 (approximately 20% of the population), emissions per person were approximately 30% higher; while with 100–1000 persons/km2 (approximately 1.5% of the population), they were approximately 70% higher; and with 10,000 persons/km2 (approximately 25% of the population), they were approximately 70% lower. A map was produced for use when considering the cities and regions suitable for a decarbonized society as well as policies such as electrification, modal shift, and coordination of urban centers.